Proinflammatory Histidyl–Transfer RNA Synthetase–Specific CD4+ T Cells in the Blood and Lungs of Patients With Idiopathic Inflammatory Myopathies. Issue 1 (26th November 2019) - Galindo‐Feria, Angeles S.; Albrecht, Inka; Fernandes‐Cerqueira, Cátia; Notarnicola, Antonella; James, Eddie A.; Herrath, Jessica; Dastmalchi, Maryam; Sandalova, Tatyana; Rönnblom, Lars; Jakobsson, Per‐Johan; Fathi, Maryam; Achour, Adnane; et al.
Abstract : Objective: Autoantibodies targeting histidyl–transfer RNA synthetase (HisRS; anti–Jo‐1) are common in the idiopathic inflammatory myopathies (IIMs) and antisynthetase syndrome. This study was undertaken to investigate immunity against HisRS in the blood and lungs of patients with IIM/antisynthetase syndrome. Methods: Bronchoalveolar lavage (BAL) fluid, BAL fluid cells, and peripheral blood mononuclear cells (PBMCs) from patients with IIM/antisynthetase syndrome (n = 24) were stimulated with full‐length HisRS protein or a HisRS‐derived peptide (HisRS11–23 ). BAL fluid and PBMCs from patients with sarcoidosis (n = 7) and healthy subjects (n = 12) were included as controls. The CD4+ T cell response was determined according to levels of CD40L up‐regulation and cytokine expression using flow cytometry. Anti–Jo‐1 autoantibody responses in the serum and BAL fluid were assessed by enzyme‐linked immunosorbent assay. Lung biopsy samples from patients with IIM/antisynthetase syndrome (n = 14) were investigated by immunohistochemistry. Results: In BAL fluid, CD4+ T cells from 3 of 4 patients with IIM/antisynthetase syndrome responded to stimulation with HisRS protein, as measured by the median fold change in CD40L expresssion in stimulated cells compared to unstimulated cells (median fold change 3.6, interquartile range [IQR] 2.7–14.7), and 2 of 3 patients with IIM/antisynthetase syndrome had the highest responses to HisRS11–23 (median fold change 88, IQR 27–149). In PBMCs, CD4+ T cells from 14 of 18 patients with IIM/antisynthetase syndrome responded to HisRS protein (median fold change 7.38, IQR 2.69–31.86; P < 0.001), whereas a HisRS11–23 response was present in 11 of 14 patients with IIM/antisynthetase syndrome (median fold change 3.4, IQR 1.87–10.9; P < 0.001). In the control group, there was a HisRS11–23 response in 3 of 7 patients with sarcoidosis (median fold change 2.09, IQR 1.45–3.29) and in 5 of 12 healthy controls (median fold change 2, IQR 1.89–2.42). CD4+ T cells from patients with IIM/antisynthetase syndrome displayed a pronounced Th1 phenotype in the BAL fluid when compared to the PBMCs ( P < 0.001), producing high amounts of interferon‐γ and interleukin‐2 following stimulation. Anti–Jo‐1 autoantibodies were detected in BAL fluid and germinal center (GC)–like structures were seen in the lung biopsy samples from patients with IIM/antisynthetase syndrome. Conclusion: The results of this study demonstrate a pronounced presence of HisRS‐reactive CD4+ T cells in PBMCs and BAL fluid cells from patients with IIM/antisynthetase syndrome as compared to patients with sarcoidosis and healthy controls. These findings, combined with the presence of anti–Jo‐1 autoantibodies in BAL fluid and GC‐like structures in the lungs, suggest that immune activation against HisRS might take place within the lungs of patients with IIM/antisynthetase syndrome.